Kaitan Fungsi Gamma terhadap Fungsi Trigonometri - Hamzi, Zaidulkhair; Mas’ud, Syamsuddin; Alimuddin, Alimuddin (JURNAL DIFERENSIAL, 2024)
This paper is a literature study on the relationship between real factorials denoted by gamma functions to trigonometric functions. The main objective of this study is to prove the relationship with a different method from what has been done by George E. Andrews in the book “special functions”. In Goerge’s paper, the connection is proved by using the definition of the gamma function in integral form. As for this paper, the proof is done by using the definition of gamma function in a form other than integral.